Antioxidant Activities Extracts N-Hexane, Ethyl Acetate and Methanol of Limau Sundai (Citrus nobilis Lour) Peels - Mai Efdi; Afrizal Afrizal; Niza Lian Pernadi; Melindra Mulia; Devi Purnamasari (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2022)
The Limau Sundai plant (Citrus Nobilis Lour) is widely known in West Sumatra. The fruit of this plant is commonly consumed as a cooking spice. This antioxidant activity test research aims to find out the potential of Lime Sundai peel as a source of antioxidant compounds. The peel of Limau Sundai fruit is ensnared with methanol solvent and concentrated using a rotary evaporator to obtain a coarse extract. The crude extract is then partitioned successively in n-hexane and ethyl acetate so that n-hexane, ethyl acetate, and methanol extracts are obtained. Sundai lime peel has good antioxidant activity against DPPH, which is shown in the ethyl fraction of acetate, methanol, and liquid methanol. The antioxidant activity of the three fractions is smaller than vitamin C and more significant than the hexane fraction. In the ethyl acetate, methanol and methanol/aqueous fractions with concentrations of 1076, 1822, and 1372 ppm in a row can reduce 50% of DPPH radical activity.